Utilização de procedimentos multivariados no consumo de água e energia elétrica em habitações sociais com sistema de aquecimento solar - Tutia, Marcelo Hiroshi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nowadays, renewable energy sources are exploited and used for the development of society and stand out for being cleaner and less polluting than non-renewable energy sources. These renewable energy sources, solar energy is one of the most exploited, used in photovoltaic systems for power generation and solar water heating systems, the second use cited the best-known and can be seen in homes, businesses and industries. The solar heating system has among its objectives, to provide energy saving because it provides hot water without the need for electrical systems, such as electric shower, which is one of the devices that consume more energy. To provide economy of energy consumption, minimize environmental impacts, redirect investments in new sources of electricity, the Government of the State of São Paulo, together with the Development Company Housing and Urban State of São Paulo - CDHU, as housing policy, installed in homes of social interest built from 2007, the solar heating system water. In Ourinhos - SP, Helena Braz Vendramini housing project was awarded the solar heating system water in homes, but in the same city, there is another housing project, the Orlando Quagliato, but being older, does not have the solar heating system, a factor that motivated this study and the search for determinants for the viability and recommendation of key features to optimize the alternative energy source to use. The objective of this research was to apply procedures and techniques of multivariate analysis in evaluating the economic impact and the pursuit of fundamental socioeconomic identifiers for the description of a rational use of water policy and energy in housing with and without solar water heating system. The results showed that differences between the housing are observed for combinations of consumption and socioeconomic variables and the association of positivity between these sets of variables was...

Atualmente, fontes de energia renováveis são exploradas e usadas para o desenvolvimento da sociedade e se destacam por serem mais limpas e menos poluentes que as fontes de energia não renováveis. Entre estas fontes de energia renováveis, a energia solar é uma das mais aproveitadas, usada em sistemas fotovoltaicos para geração de energia elétrica e em sistemas de aquecimento solar de água, sendo a segunda utilização citada a mais conhecida, podendo ser vista em residências, comércios e indústrias. O sistema de aquecimento solar tem entre seus objetivos, o de proporcionar economia de energia elétrica, pois fornece água quente sem a necessidade de utilizar sistemas elétricos, como o chuveiro elétrico, que é um dos aparelhos que mais consome energia. Para proporcionar economia do consumo de energia elétrica, minimizar impactos ambientais, redirecionar investimentos em novas fontes geradoras de energia elétrica, o Governo do Estado de São Paulo, em conjunto com a Companhia de Desenvolvimento Habitacional e Urbano do Estado de São Paulo - CDHU, como política de habitação, instalaram, nas residências de interesse social construídas a partir de 2007, o sistema de aquecimento solar de água. Na cidade de Ourinhos - SP, o conjunto habitacional Helena Braz Vendramini foi contemplado pelo sistema de aquecimento solar de água nas residências, porém, na mesma cidade, existe outro conjunto habitacional, o Orlando Quagliato, mas, por ser mais antigo, não possui o sistema de aquecimento solar, fator que motivou o presente estudo quanto à busca de determinantes para a viabilização e recomendação de características fundamentais para a otimização do aproveitamento de fonte de energia alternativa. O objetivo desta pesquisa foi aplicar procedimentos e técnicas de análise multivariada na avaliação do impacto econômico e na busca dos identificadores socioeconômicos fundamentais ...
Multivariate procedures for use in water consumption and electricity in social housing with solar heating system
Keywords: Aquecedores solares de agua; Analise multivariada; Habitação popular; Solar water heaters